ANALISIS KESUKSESAN SISTEM INFORMASI ONLINE LAYANAN ADMINISTRASI DI KEMENTERIAN DALAM NEGERI - Muhammad Ikhsan; Azhar Kasim (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This research focuses on the successful implementation of e-government through the Online Information System for Administrative Services (SIOLA) at the Ministry of Home Affairs (Kemendagri). The purpose of this application is to improve service quality and create services that are effective, efficient, fast, easy, and all services can be processed online without manual service. In its application, this application still experiences several problems, namely services that have not been fully carried out online and some services that are not actively used. Using a post-positivism approach, researchers assessed the success of implementing information systems for administrative services to determine the extent of the role of these information systems in supporting the service process at the Ministry of Home Affairs. Using data collection techniques through interviews and documentation studies as well as literature studies using the IS Success Model theory by DeLone and McLean (2003) which consists of 6 (six) variables namely system quality, information quality, service quality, intention to use/use, user satisfaction, and net benefit, researchers obtain data as a basis for evaluating the success of e-government implementation through the SIOLA application. The results of the study show that the success rate of implementing e-government through the SIOLA application at the Ministry of Home Affairs has been going well but not optimal, because there are still indicators on the variables used to measure the success rate of information systems that have not been met.